Analisis Determinan Investasi Asing Langsung (FDI) Kelompok Negara Middle Income di ASEAN - Sectio Merian.M; Hasdi Aimon (Universitas Negeri Padang, 2024)
The purpose of this research is to ascertain how trade openness, market size, Economic Growth and exchange rates on foreign direct investment in five middle incomes countries. In five middle-income ASEAN nations, trade openness, market size, economic development, and currency rate all have an impact on foreign direct investment. This kind of study combines quantitative research with secondary data in the form of panel data, which is a cross-sectional analysis of five middle-income ASEAN countries and time series data from 2002 to 2022. Panel data analysis is the method of analysis that is employed. The findings demonstrated that: (1) In five middle-income ASEAN nations, trade openness significantly and favourably affects foreign direct investment. The impact of market size on foreign direct investment is noteworthy and beneficial in five ASEAN nations with middle-class incomes. (3) In five middle-income ASEAN nations, economic growth has a very favourable and large impact on foreign direct investment. (4) In five ASEAN middle-income nations, the exchange rate has a favourable and considerable impact on foreign direct investment.